Zero-Waste Kitchen: Circular Economy-Based Kitchen Waste Management Strategy in Sustainable Tourism Restaurants - Rossy Luckita Sasmita (PT ARFA DIGITAL TECHNOLOGY, 2025)
The restaurant industry in the tourism sector faces major challenges related to food waste and waste management, which can be detrimental both economically and environmentally. This study aims to explore the application of Zero-Waste Kitchen based on Circular Economy in sustainable tourism restaurants. The main objective of this study is to identify the challenges faced by restaurants in implementing this model, the best practices used, the role of technology, as well as the impact of government policies. The study uses a qualitative approach with a case study design, which includes semi-structured interviews, participatory observations, and documentation analysis on five restaurants that have adopted the Zero-Waste principle. The research findings show that the main challenges faced by restaurants are the high initial investment costs, difficulties in managing non-organic waste, and a lack of awareness among staff and customers. On the other hand, best practices such as the reuse of food waste and the processing of organic waste into compost have shown positive results. Technology, such as IoT and food waste monitoring systems, play an important role in supporting the sustainability of restaurant operations. Government policies that support through fiscal incentives and waste management infrastructure are also found to be very important. This research contributes to the sustainability literature in the tourism restaurant sector and provides recommendations for restaurants to overcome challenges in implementing Zero-Waste based on Circular Economy.